Penggunaan Flash Card dalam Meningkatkan Pengetahuan dan Praktik Pemberantasan Sarang Nyamuk (PSN) 3M Plus pada Tanggap Bocah (Tabo) di Dusun Sidomulyo - Fitria Indah Hikmawati (Awatara Publisher, 2025)
Currently, Dengue Hemorrhagic Fever (DHF) remains a public health issue in Sleman Regency. The disease can be controlled through the Mosquito Nest Eradication Program 3M Plus. Various methods can be used to disseminate information about PSN 3M Plus to the community, one of which is through the use of Flash Cards. This study aims to determine whether the use of Flash Cards can improve knowledge and practices of PSN 3M Plus among Tanggap Bocah (Tabo) members in Sidomulyo Hamlet. This research is a quasi-experimental study with a Non-Equivalent Control Group design. The sampling technique used was purposive sampling. The subjects of this study were 40 Tabo members, consisting of 20 from Sidomulyo Hamlet and 20 from Kalirase Hamlet. Data analysis was conducted descriptively and analytically using the Wilcoxon test, Paired Sample T-Test, and Mann-Whitney test. The results showed an increase in knowledge and practices of PSN 3M Plus, as indicated by the difference in pre-test and post-test scores after the Flash Card intervention. Both the knowledge and practice variables showed statistically significant improvements (p <0,05). Furtheremore, the difference in knowledge and practices score between the Flash Card and the lecture method showed that Flash Cards were more effective than lectures in improving knowledge and practices related to PSN 3M Plus among Tabo members (p <0,05).